Gadd45γ regulates cardiomyocyte death and post-myocardial infarction left ventricular remodelling. (15th September 2015) - Lucas, Alexandre; Mialet-Perez, Jeanne; Daviaud, Danièle; Parini, Angelo; Marber, Michael S.; Sicard, Pierre
Abstract: Aims: Post-infarction remodelling is accompanied and influenced by perturbations in mitogen-activated protein kinase (MAPK) signalling. The growth arrest and DNA-damage-inducible 45 (Gadd45) proteins are small acidic proteins involved in DNA repair and modulation of MAPK activity. Little is known about the role of Gadd45 in the heart. Here, we explored the potential contribution of Gadd45 gamma ( γ ) isoform to the acute and late phase of heart failure (HF) after myocardial infarction (MI) and determined the mechanisms underlying Gadd45 γ actions. Methods and results: The Gadd45 γ isoform is up-regulated in murine cardiomyocytes subjected to simulated ischaemia and in the mouse heart during MI. To mimic the situation observed during MI, we enhanced Gadd45 γ content in cardiomyocytes with a single injection of an adeno-associated viral (AAV9) vector encoding Gadd45 γ under the cTNT promoter. Gadd45 γ overexpression induces cardiomyocyte apoptosis, fibrosis, left ventricular dysfunction, and HF. On the other hand, genetic deletion of Gadd45 γ in knockout mice confers resistance to ischaemic injury, at least in part by limiting cardiomyocyte apoptosis. Mechanistically, Gadd45 γ activates receptor-interacting protein 1 (RIP1) and caspase-8 in a p38 MAPK-dependent manner to promote cardiomyocyte death. Conclusion: This work is the first to demonstrate that Gadd45 γ accumulation during MI promotes the development and persistence of HF by inducing cardiomyocyte apoptosis in a p38 MAPK-dependent manner. We clearly identify Gadd45 γ as a therapeutic target in the development of HF.